Thrombolytic, CNS Depressant and Anti-Diarrhoeal Activities of Ethanolic Extract of Bark of Syzygium cumini L. Skeels: An In-Vivo and In-Vitro Study - Fokhrul Abedin; Md. Saddam Hussain; Areful Islam; Niloy Sen; Abhijit Das; Auditi Kar; Md. Monir Hossain; Md.ShalahuddinMillat; Mohammad Safiqul Islam (Journal of Pharmacy and Nutrition Sciences, 2018)
The present study was aimed to create scientific insights that validate the traditional use of bark of ethanolic extract of S. cumini in thrombosis, CNS depression and in diarrheal cases. The CNS depressant activity was evaluated by observing the locomotor activity of the animals in the open field and forced swim methods at a dose of 200 and 400 mg/kg body weight and the anti-diarrheal activity was evaluated through castor oil induced method and charcoal induced GI motility tests. Finally thrombolytic activity assessment was done by employing Streptokinase as standard. In this study, among the five different concentrations 10 mg/ml showed maximum clot lysis that was 48.5%, whereas standard showed 51.05% lysis of clot. In case of open field test, the mean number of movement at 60 min were 20 and 31.11 at a dose of 200 and 400 mg/kg respectively. In case of castor oil induced method the above two doses of bark extract of S. cumini exhibited 23.07% and 36.67% of diarrheal inhibition compared to the standard Loperamide (5mg/kg) was 50%. For charcoal induced GI motility test, diarrheal inhibition was 23.07% and 36.67%. The present revealed that ethanolic bark extract of bark of S. cumini justify its traditional uses through good thrombolytic, CNS depressant and anti-diarrheal activity.